An Egyptian Partially Gilded Bronze Group Statue: Examination and Analysis. (25th April 2014) - Ghoneim, M.
Abstract : This paper aims at examining and analysing an Egyptian partially gilded bronze group statue excavated from the San al‐hagar (Tanis) site and housed in the Egyptian Museum in Cairo in October 2007. It has deteriorated severely and is covered with an extremely disfiguring and heterogeneous crust that varies in colour, thickness and nature, and that is incorporated with soil particles in many parts. The gilding layer sandwiched between, under and above the corrosion products suffers from rupture, flaking and detachment. Examination and analysis were performed using optical microscopy (OM), an X‐ray diffractometer, equipped with an X‐ray fluorescence spectrometer (XRDF), and scanning electron microscopy, equipped with energy‐dispersive spectrometry (SEM–EDS). The study examined the nature and the chemical composition of the corrosion products, the body metal and the gilding layer. This study also discusses the corrosion phenomenon and the nature of the burial soil, and detects the decoration technology of the gilding.